Adaptive evolution of koala retrovirus transcription silencing and what it means for conservation - Keith J. Chappell; Michaela B. J. Blyton; Zhiping Weng; William E. Theurkauf (Clinical and Translational Medicine)
Abstract Koala populations in Australia face a barrage of threats, chiefly, habitat degradation and the effects of climate change including drought and bushfire. Further, high rates of chlamydiosis, linked to koala retrovirus (KoRV) viral load, is a major contributing factor to northern population decline. However, recent work by Yu et al., (Cell, 2024) has provided a glimmer of hope: some koalas have evolved ‘adaptive genome immunity’, which is able to actively suppress endogenous KoRV transcription. A single KoRV‐A provirus insertion within MAP4K4 gene's 3’ UTR is shown to be the trigger for production of sense and anti‐sense piRNAs, and that MAP4K4 KoRV integration is linked to both a 20% reduction in proviral genome integrations and 10‐fold reduction of KoRV transcription within male germline tissue. Here we discuss how this finding offers the potential to reduce koala disease burden and can be incorporated into conservation management to help save this iconic species.